A Model of the Influence of English Language Competence on Business Performance through Management Effectiveness - Donny Hendry Fahsani; Sujana Sujana; Cecilia Valentina Sri Hadi; Rini Syarif (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing globalization of business has elevated English language competence from a general communication skill to a strategic managerial capability. However, empirical evidence explaining how English language competence contributes to business performance remains limited. This study aims to examine the influence of English language competence on business performance, with management effectiveness positioned as a mediating mechanism. Using a quantitative explanatory approach, data were collected through a cross-sectional survey of 185 business owners and managerial-level employees in an emerging economy context. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that English language competence has a significant positive effect on management effectiveness and business performance. Management effectiveness also significantly influences business performance and partially mediates the relationship between English language competence and business performance. These findings indicate that English language competence enhances business performance not only through direct channels, such as improved external communication, but also indirectly by strengthening managerial decision-making, coordination, leadership, and control. This study contributes to the literature by repositioning English language competence as a strategic managerial capability rather than a standalone soft skill and by providing a process-oriented explanation of its impact on business performance. Practically, the findings suggest that organizations and MSMEs should integrate English language development into managerial training and leadership development programs. From a policy perspective, the study highlights the importance of aligning management education and professional certification with global communication competencies, particularly in emerging economies.   Keywords: English language competence; management effectiveness; business performance; managerial capability; emerging economies; PLS-SEM